2010
DOI: 10.4040/jkan.2010.40.2.191
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Physical Activity in Korean Older Adults: Distinction between Urban and Rural Areas

Abstract: Purpose:The aim of this study was to compare the predictors of physical activity between urban and rural dwelling Korean older adults. Methods: This study was a cross-sectional descriptive survey. A self-report questionnaire or face to face interviews were used to collect data from 336 older adults (urban: 129, rural: 207) (OR= 0.799, p<.001) were significant factors predicting physical activity in urban elders. Conclusion: These findings provide information that is relevant in designing interventions to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 19 publications
3
21
0
2
Order By: Relevance
“…In our study, physical inactivity was not found to be a contributing factor to depression. This inconsistency might have been due to the ceiling effect, as our participants had a relatively high level of physical activity compared to older Koreans overall (Park & Park, ). We also found no differences in physical activity between male and female participants.…”
Section: Discussionmentioning
confidence: 84%
“…In our study, physical inactivity was not found to be a contributing factor to depression. This inconsistency might have been due to the ceiling effect, as our participants had a relatively high level of physical activity compared to older Koreans overall (Park & Park, ). We also found no differences in physical activity between male and female participants.…”
Section: Discussionmentioning
confidence: 84%
“…In particular, older women in rural communities may be more vulnerable to UI as they face a different set of challenges compared to urban women. Park and Park [7] found that compared to urban elders, rural elders had lower educational level, more chronic illnesses, poorer nutritional status, higher level of depression, and less time spent outdoors during daytime. Although research has shown positive impact of UI self-management programs for community-dwelling older women in Korea [8], no to little progress has been made on developing such programs for older women over the past decades, partly due to difficulties reaching out to affected populations when they are reluctant to disclose bladder problems [9] or because they consider UI as a normal ageing process [10].…”
Section: Introductionmentioning
confidence: 98%
“…Studies on the measurement of physical activity in the elderly in Korea (Park, 2007; Park & Park, 2010) have mostly used a self‐reporting method, and validity of self‐reported value measures are low (Sallis & Saelens, 2000). Actigraph accelerometers show high accuracy compared to earlier equipment, given the recording activity intensity, frequency, and time (Hendelman et al ., 2000).…”
Section: Introductionmentioning
confidence: 99%